GAMBARAN CARING PENGASUH DALAM PEMENUHAN KEBUTUHAN DASAR LANSIA - Febrina, Wiwit; Rezkiki, Fitrianola; Rahmiwati, Rahmiwati; Dearianto, Chelsye Marviyouna (HUMAN CARE JOURNAL, 2024)
Entering old age, a person experiences a process of changing body functions both physically and psychologically which can cause the elderly to have difficulty in achieving their basic needs. The Caring behavior is a form of support that caregivers can provide to the elderly in an effort to protect, improve, maintain or devote a sense of humanity by helping someone achieve a better aspect. This study aimed to determine the caring behavior of caregivers in fulfilling basic needs for the elderly at Kasih Sayang Ibu Tresna Werdha Social Homes Batusangkar West Sumatera Province in 2022. This study was conducted on March untill July in 2022. The text describes a qualitative research with a phenomenological approach. The research population consists of all elderly individuals who directly receive caring behavior from caregivers, using interview guidelines. Purposive sampling was employed based on inclusion and exclusion criteria. In the qualitative study, two themes were identified: the optimal ability of the elderly to fulfill basic needs and the ineffectiveness of communication between caregivers and the elderly in meeting their basic needs. The study concludes that the majority of the elderly evaluate the caregiving behavior of caregivers as good. Elderly individuals with the ability to perform activities independently find it easier to meet their basic needs with minimal caregiver assistance. The research suggests that caregivers should continue to enhance caregiving processes for the elderly to achieve optimal basic needs fulfillment through effective communication between caregivers and the elderly.